L-Arginine abrogates maternal and pre-pubertal codeine exposure-induced impaired spermatogenesis and sperm quality by modulating the levels of mRNA encoding spermatogenic genes - Akhigbe, Roland Eghoghosoa; Afolabi, Oladele A.; Ajayi, Ayodeji Folorusho (Frontiers in Endocrinology, 2023)
This study investigated the impact of maternal and prepubertal codeine exposure on spermatogenesis and sperm quality in F1 male Wistar rats to study the effect that codeine may have during recreational use in humans. Also, the effect of arginine supplementation on codeine-induced alteration in spermatogenesis and sperm quality was evaluated. Female rats were treated with either 0.5 ml distilled water or codeine orally for eight weeks, and then mated with male rats (female:male, 2:1). The F1 male offsprings of both cohorts were weaned at 3 weeks old and administered distilled water, codeine, arginine, or codeine with arginine orally for eight weeks. Prepubertal codeine exposure in rats whose dams (female parents) were exposed to codeine delayed puberty and reduced the weight at puberty. Prepubertal codeine exposure exacerbated maternal codeine exposure-induced reduced total and daily spermatid production, sperm count, sperm motility, and normal sperm form, as well as impaired sperm plasma membrane integrity and increased not intact acrosome and damaged sperm DNA integrity. These perturbations were accompanied by a decrease in mRNA levels encoding spermatogenic genes, testicular testosterone and androgen receptor (AR) concentrations, and upregulation of sperm 8-hydroxydeoxyguanosine (8OHdG). Prepubertal arginine supplementation mitigated codeine-induced alterations. This study provides novel experimental evidence that maternal and prepubertal codeine exposure reprogramed spermatogenesis and sperm quality of male FI generation by decreasing mRNA levels encoding spermatogenic genes and AR via oxidative stress-mediated signaling, which was abrogated by prepubertal arginine supplementation.